Socio-cultural practices and improved cooking stove technology choices among agro-pastoral communities in Arumeru District, Tanzania - Luka Njau; George Matto (Interdisciplinary Journal of Rural and Community Studies, 2024)
This study assessed the socio-cultural factors influencing the choice of improved cooking stove technology among agro-pastoral communities in Arumeru District, Arusha region. The study used a cross-sectional research design and was conducted in four villages. Two categories of respondents were involved in the study. The first category consisted of 37 participants interviewed as Key Informants (KIs) and through focus group discussions (FGDs). The second category who responded to the questionnaire involved 92 respondents who had benefited from the alternative cooking energy technologies programme. Both qualitative and quantitative data were collected, with a greater emphasis on qualitative data. Content analysis was used to analyse the qualitative data, while the quantitative data were analysed using Statistical Package for Social Sciences (SPSS) computer software. The study found the persistence of certain socio-cultural practices that encourage the use of traditional three-stone stoves over improved stoves. These practices include preferences for food cooked using traditional three-stone stoves and the tradition of formally handing over the traditional cooking stoves to a newly married woman in the household, among others. It is concluded that while some community members consider these practices positive and valuable, they largely contribute to high biomass consumption and, therefore, the likelihood of environmental degradation. It is recommended that serious sensitisation and training programmes, among other recommendations detailed in this study, be conducted.